Front Cover: Excited‐State Topology Modifications of the Dihydroazulene Photoswitch Through Aromaticity (ChemPhotoChem 8/2019). Issue 8 (18th July 2019) - Skov, Anders B.; Ree, Nicolai; Gertsen, Anders S.; Chabera, Pavel; Uhlig, Jens; Lissau, Jonas S.; Nucci, Luigi; Pullerits, Tõnu; Mikkelsen, Kurt V.; Brøndsted Nielsen, Mogens; Sølling, Theis I.; Hansen, Thorsten
Abstract : The Front Cover illustrates the drastically changed dynamics of the dihydroazulene photoswitch upon annulation with a benzene ring. The introduced excited‐state aromaticity enhances an excited‐state barrier for the benzannulated species (lower panel) so that the conical intersection to the photoproduct can no longer be reached. The potential energy surfaces no longer match, and can be likened to a badly designed video game level, which cannot be completed. More information can be found in the Article by A. B. Skov et al. onpage 619 in Issue 8, 2019 (DOI:10.1002/cptc.201900088 ).